Pengembangan Soft Skill Mahasiswa Melalui Program Merdeka Belajar Kampus Merdeka Asistensi Mengajar - Sani, Stefhan Anselmus Lamen; Kemba, Lusia Faustin Nadia; Gago, Jumilla; Raja, Yohana Mi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Muthmainna Ende Private Islamic Junior High School as a partner of the activity faces challenges in developing active, innovative, and technology-based learning due to limited teacher resources and suboptimal contextual training, thus requiring immediate solutions to improve the quality of education. The purpose of this community service activity is to develop the soft skills of FKIP Universitas Flores students through active involvement in the Teaching Assistance program at partner educational units. The activity was carried out using a three-stage method, namely preparation (briefing, observation, FGD), implementation (teaching assistance, P5 mentoring, reflection), and closing (final report, program evaluation). The results of the activity showed a significant increase in students' soft skills such as communication, collaboration, problem-solving, leadership, and mastery of learning technology. In conclusion, the MBKM Teaching Assistance program has proven effective as a strategic tool in strengthening pedagogical competence and developing students' soft skills, while also having a positive impact on partner schools.